1997
DOI: 10.1007/s007750050159
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic studies on the reactions of Fusarium galactose oxidase with five different substrates in the presence of dioxygen

Abstract: Reactions (25 7C) of galactose oxidase, GOase ox from Fusarium NRRL 2903 with five different primary-alcohol-containing substrates RCH 2 OH:-D-galactose (I) and 2-deoxy-D-galactose (II) (monosaccharides); methyl-b-D-galactopyranoside (III) (glycoside); D-raffinose (IV) (trisaccharide); and dihydroxyacetone (V) have been studied in the presence of O 2 . The GOase ox state has a tyrosyl radical coordinated at a square-pyramidal Cu II active site, and is a two-equivalent oxidant. Reactant concentrations were [GOa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(33 citation statements)
references
References 24 publications
5
27
1
Order By: Relevance
“…The values for k cat and K m (H 2 -OMeGal), Table 1, are in agreement with literature reports of 1180 s −1 and 175 mM for reaction of GAOX with galactose at 20 °C and pH 7.0 24. The value for k cat /K m (H 2 -OMeGal) compares favorably with reported second-order rate constants in the range of 1 × 10 4 M −1 s −1 3,4. The much faster value of k cat /K m (O 2 ), 2.6(0.3) × 10 6 m −1 s −1 , is also in the range of previously reported values for second-order rate constants of 8 × 10 6 M −1 s −1 at 4 °C and 1 × 10 7 M −1 s −1 at 25 °C 3,4.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…The values for k cat and K m (H 2 -OMeGal), Table 1, are in agreement with literature reports of 1180 s −1 and 175 mM for reaction of GAOX with galactose at 20 °C and pH 7.0 24. The value for k cat /K m (H 2 -OMeGal) compares favorably with reported second-order rate constants in the range of 1 × 10 4 M −1 s −1 3,4. The much faster value of k cat /K m (O 2 ), 2.6(0.3) × 10 6 m −1 s −1 , is also in the range of previously reported values for second-order rate constants of 8 × 10 6 M −1 s −1 at 4 °C and 1 × 10 7 M −1 s −1 at 25 °C 3,4.…”
Section: Discussionsupporting
confidence: 90%
“…The value for k cat /K m (H 2 -OMeGal) compares favorably with reported second-order rate constants in the range of 1 × 10 4 M −1 s −1 3,4. The much faster value of k cat /K m (O 2 ), 2.6(0.3) × 10 6 m −1 s −1 , is also in the range of previously reported values for second-order rate constants of 8 × 10 6 M −1 s −1 at 4 °C and 1 × 10 7 M −1 s −1 at 25 °C 3,4. However, prior efforts to obtain K m (O 2 ) for galactose oxidase were unsuccessful and it was concluded that the enzyme could not be saturated with oxygen 24,25.…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…The sample solution was stirred at 480 rpm and the electrode calibrated in air-saturated Milli-Q water (z 0.252 mM O 2 ). 50 In each measurement, air bubbles were excluded before the start of the measurement. 50 ml of free or immobilized enzyme (stored on ice) was injected into a 3 ml reaction mixture of air-saturated 5-400 mM galactose and 1 mM K 3 [Fe(CN) 6 ] in buffer (pH 7.0) at 25 C through the access slot using a syringe.…”
Section: Assays Of Enzyme Activitymentioning
confidence: 99%